Mixing times in a stirred vessel with a modified turbine - Bombač, Andrej (Acta chimica slovenica, 2012)
We present a mixing-time analysis for a double-disk turbine (DDT, SI Pat.No. 22243) and the well-known Rushton turbine (RuT) based on liquid stirring in a baffled vessel. The mixing time was measured locally based on the pulse/response technique. A small quantity of hot water, poured into the liquid bulk, just above the measurement location, was used as the pulse, while the change in the liquid temperature represented the system response. The results were obtained in two ways: (i) from measurements on the set-up and (ii) based on a CFD analysis. The pouring of the hot water was numerically simulated through the initialization of the scalar field. The duration of the temperature-pulse initialization around the measuring location corresponded to the pouring time in the experiment. All the energy introduced was freely swept away by the flow. The CFD-analyzed mixing times were consistently higher than the measured ones across the whole testing range, from 150 to 460 min1. When comparing our mixing-time results with those from the literature based on a dimensionless mixing time we found them to be in good agreement.
Keywords: computational fluid dynamics; čas mešanja; dinamika tekočin; double-disk turbine; mixing power; mixing time; moč mešanja; temperature response; temperaturni odziv; turbinska mešala